Impact of Different Extraction Solvents on Bioactive Compounds and Antioxidant Capacity from the Root of Salacia chinensis L. - Thanh Van Ngo; Christopher James Scarlett; Michael Christian Bowyer; Phuong Duc Ngo; Quan Van Vuong (Journal of Food Quality)
This study aimed to study the impact of selected common organic solvents on extractable solids, phytochemical composition, and antioxidant capacity of S. chinensis. The results showed that the tested solvents played an important role in extraction of total solid and phytochemical composition as well as antioxidant capacity of S. chinensis. Acetone (50% v/v) was found to be the optimal extraction solvent for extractable solids (12.2%), phenolic compounds (60 mg GAE/g DW), flavonoids (100 mg CE/g DW), proanthocyanidins (47.4 mg CE/g DW), and saponins (754 mg EE/g DW) as well as antioxidant capacity (ABTS 334 mM TE/g DW, DPPH 470 mM TE/g DW, FRAP 347 mM TE/g DW, and CUPRAC 310 mM TE/g DW). The extract prepared from 50% acetone had high levels of bioactive compounds (TPC 555 mg GAE/g CRE, flavonoids 819 mg CE/g CRE, proanthocyanidins 392 mg CE/g CRE, and saponins 1,880 mg EE/g CRE) as well as antioxidant capacity (ABTS 414 mM TE/g, DPPH 407 mM TE/g, FRAP 320 mg TE/g, and CUPRAC 623 mM TE/g), thus further confirming that 50% acetone is the solvent of choice. Therefore, 50% acetone is recommended for extraction of phenolic compounds, their secondary metabolites, saponins, and antioxidant capacity from the root of S. chinensis for further isolation and utilisation.